Discourse analysis on conversational turn-taking in a German film by Jan Ole Gerster - Farid Rizal, Nur Farhana (2021)
Turn-taking is an important mechanism in order to make a conversation flows efficiently. It occurs in dialogues and conversation where everyone uses it but not everyone aware of the strategies that available. Kato (2000) stated that turn-taking that occurs in conversation might differs between different cultures and languages which could be found as burdensome to the foreign language learners. Lacking of studies of turn-taking in German film conversation make the researchers, German language educators and graduate students whose in the discourse field barely have medium or sources to explore the language naturally. This study is based on the turn-taking analysis of conversation in a German film “A Coffee in Berlin” by Jan Ole Gerster which is also a good film to represent the typical German language and culture that is suitable for German language beginners and fans to watch (Blankenship & Twark, 2017). This film also uses German language as the main language for conversation and contains many scenes that involve daily life conversation of the Germans. Daily life conversation is chosen in this film as it can be understood by a bigger audience especially for language learners at beginner’s level. By referring to this film, this study aims to detect the turn-taking rules and analyse the turn-taking strategies that occurs in the film according to Sacks, Schegloff and Jefferson (1974). The conversation data collected are transcribed by applying Gesprächsanalytisches Transkriptionssystem 2 which means discourse and conversation- analytic transcription 2, or also known as GAT 2 by Selting (2009) as it is the most compatible transcription with German language. This study also is considered as qualitative descriptive study as it describes the data and analyse them parallel with what Nassaji (2015) has stated, descriptive qualitative study is fit to the study of foreign language learning. This study found that three rules of turn-taking; Current speaker selects next, Next speaker self-selects and Current speaker continues are involved in the conversation of the film. There are also several strategies being analysed in the study from the rules found, used by the characters in the film. In short, this study hope that the study will benefits the German language educators and researchers in order to practice and explore the German turn taking and naturally.